Development of a fidelity measure for community integration programmes for people with acquired brain injury. (17th November 2014) - Parvaneh, Shahriar; Cocks, Errol; Buchanan, Angus; Ghahari, Setareh
Abstract: Objective : The paper describes development of the Assessment of Community Integration Programme Attributes (ACIPA) measure based on a descriptive community integration framework. The purpose of this measure is to allow evaluation of community integration programmes for adults with acquired brain injury (ABI). Methods : The Community Integration Framework (CIF) was used to design a fidelity evaluation measure through consultation with 37 participants from five stakeholder groups (practitioners, researchers, policy-makers, people with ABI and family members of people with ABI) using semi-structured interviews, focus groups, iterative surveys and a multi-attribute utility (MAU) method. Results : The resultant measure included seven themes and 21 attributes. Each attribute included indicators and probing questions. Weights were assigned to each theme and constituent attributes. Conclusion : Programme evaluation commonly focuses on outcomes, often overlooking analysis of programme processes. Although it requires further psychometric (reliability and validity) development, the Assessment of Community Integration Programme Attributes may be used to assess the relationship between programme processes and specific outcomes and also to inform the development of programmes aiming to enhance community integration for adults with ABI.